Assessment of Cardiac Effect of Preeclampsia. Right Ventricular Function Analysis Using Speckle Tracking Echocardiography: Penilaian Efek Jantung dari Preeklampsia. Analisis Fungsi Ventrikel Kanan Menggunakan Ekokardiografi Pelacakan Spekel - AL- Muhana , Manal Yahya I.; Dujeli , Amina A B AL (Universitas Muhammadiyah Sidoarjo, 2025)
Introduction, Preeclampsia is a hypertensive disorder of pregnancy that has significant implications for cardiac function, particularly on the right ventricle (RV). Research has shown that speckle tracking echocardiography (STE) is a valuable tool in evaluating subtle RV dysfunction that might not be detected by traditional methods. Method: Pregnant ladies with preeclampsia (n= 50) compare to normotensive pregnant women (n= 50) regarded as control. Echocardiography done for them by speckle tracking to evaluate function of right ventricle. Result: There was significant difference in right ventricular function, in right ventricular longitudinal strain from normotensive pregnant women by speckle tracking echo cardio graph (-16.1±2.05 vs -17.3±1.9). Conclusion: Hypertensive disease of pregnancy including preeclampsia affect the myocardial performance, this can be diagnosed by decrease in global longitudinal strain of right ventricle by speckle tracking echocardiography. Highlights: Preeclampsia affects right ventricular function, detectable via speckle tracking echocardiography. Compared 50 preeclamptic and 50 normotensive pregnant women using echocardiography. Reduced right ventricular longitudinal strain in preeclampsia (-16.1±2.05 vs -17.3±1.9). Keywords: preeclampsia, speckle tracking echocardiography, right ventricle, global longitudinal strain